Peran Perempuan Tunisia dalam Politik Pasca-Arab Spring Melalui Telaah State Feminism - Ayu Maulida Alkholid; Firmanda Taufiq (Jurnal ICMES, 2021)
Tunisia is one of the Arab countries hit by political upheaval in the Arab Spring era. The country is considered successful through a relatively stable political transition from authoritarianism to democracy. In this process, Tunisian women have a significant role. This paper aims to describe the feminist movement, which was spearheaded by both the state and women, plays an essential role in the political constellation of Tunisia. Tunisian women had an important role in inviting and mobilizing the masses when the Arab Spring erupted. Post-Arab Spring, they were effectively involved in the political process, including drafting laws in parliament. The law ratified in 2014 is seen as more guaranteeing gender justice. This research was conducted with a qualitative method that utilizes literature studies and implements the concept of state feminism. The results of this study conclude that state feminism has changed the pattern of the political system to be more accommodating to the interests and rights of women and seek to create gender justice in Tunisia.